Risk factors and context of men who physically abuse in Bogotá, Colombia (2000)
The aim of this study was to identify risk factors for physical abuse caused by male perpetrators, as well as to describe the context of abuse and the role of the female partner in these cases in Bogotá, Colombia. Information from in-depth interviews of males reported to authorities for physical child abuse and their female partners (n = 45) was quantitatively and qualitatively analyzed and compared to to males and their female partners from the same neighborhood living with a child of the same gender and age (±3 years) as the abused child (n = 44). Situations of abuse occurred more often on a weekday, in the afternoon or early evening hours, with the mother present, exceptionally involved substance abuse, and tended to be repetititve. Male subjects’ lower level of education, stepfather status, perceived stress, substance abuse and mental illness, lack of social support, history of childhood physical abuse, negative perceptions, attributions and unrealistic expectations of the child’s behavior were associated with abuse. Cases’ female partners were more likely to have a lower occupational level, a higher frequency of dependent personality, a history of childhood physical and sexual abuse and be herself physically and emotionally abused by her spouse. At least three scenarios for abuse emerged from the analyses: “explosive” men, “abusive disciplinarians,” and “children out of parental control.” Most of the findings are consistent with existing research despite the different social and cultural context. The different scenarios suggest the need to tailor preventive and rehabilitative interventions for abusers.